Communicating with the public: opportunities and rewards for individual ecologists. Issue 6 (1st August 2010) - Pace, Michael L; Hampton, Stephanie E; Limburg, Karin E; Bennett, Elena M; Cook, Elizabeth M; Davis, Ann E; Grove, J Morgan; Kaneshiro, Kenneth Y; LaDeau, Shannon L; Likens, Gene E; McKnight, Diane M; Richardson, David C; et al.
Abstract : Many ecologists are interested in communicating science to the public and addressing societal concerns about environmental issues. Individual ecologists need to consider whether, when, and how this should be done. We propose that public outreach activities can be beneficial for ecologists at all stages of their career. There are diverse opportunities for such involvement, and these can vary enormously in terms of time and expertise required. Trends within the science of ecology, especially research focused on social–ecological systems, are likely to promote increased interactions with stakeholders and policy makers. To be effective in these interactions, ecologists should consider new approaches to communication and be aware of the potential roles scientists can play in public policy debates. Professional ecologists need to engage with non‐scientific audiences; a review of such activities should be included in considerations for promotion, recognition, and awards, while also acknowledging variations in the inclinations and abilities of individual scientists. There are, however, few current standards for how much time ecologists should commit to public outreach, how time allocation might change over a career, or how to evaluate the quality of such activities. We ask ecologists to consider ways to evaluate the quality of interactions with the public and how to reward these efforts appropriately.